PENERAPAN KEADILAN RESTORATIF DALAM TINDAK PIDANA KEPEMILIKAN SATWA LANGKA YANG DILINDUNGI DI INDONESIA - Putrawan, I Nyoman Gede; Kristiawanto, Kristiawanto; Basuki, Basuki (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to provide a juridical analysis of the ownership of protected wildlife by members of the public and to examine relevant law enforcement approaches, including the potential application of restorative justice. The issues addressed focus on the legal construction governing the ownership of protected wildlife, the formulation of criminal liability under statutory regulations, and the manner in which law enforcement may be implemented proportionally without undermining conservation objectives.The research employs a normative legal method using a statutory approach, a conceptual approach, and a systematic approach. The primary legal materials include the 1945 Constitution of the Republic of Indonesia, particularly Article 33 paragraph (3), Undang-Undang Nomor 5 Tahun 1990 tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya as amended by Undang-Undang Nomor 32 Tahun 2024, as well as implementing regulations such as Peraturan Pemerintah Nomor 7 Tahun 1999 tentang Pengawetan Jenis Tumbuhan dan Satwa and Peraturan Pemerintah Nomor 8 Tahun 1999 tentang Pemanfaatan Jenis Tumbuhan dan Satwa Liar. The study also considers Indonesia’s international commitments within the framework of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). The findings indicate that protected wildlife falls under the regime of state control based on the principle of the state’s right to control natural resources as stipulated in Article 33 paragraph (3) of the Constitution. Unauthorized ownership of protected wildlife constitutes a formal criminal offense, which is deemed complete at the moment a person possesses or maintains protected species without lawful authorization, without the need to prove concrete ecological damage. Socio-cultural reasons, tradition, or ignorance of the law do not qualify as justifications or excuses under Indonesian criminal law. From an environmental law perspective, illegal ownership contradicts the precautionary principle and the principle of sustainable development, as it has the potential to disrupt ecosystem balance and accelerate species extinction. Nevertheless, in practical law enforcement, the principle of proportionality must be applied by distinguishing between offenders involved in organized illegal wildlife trade networks and non-commercial individual offenders. Under certain circumstances, restorative justice may be considered as an alternative resolution, provided that ecological restoration is ensured and conservation objectives are not weakened. This study concludes that unauthorized ownership of protected wildlife by the public constitutes an unlawful act and must be regarded as a threat to the sustainability of national biodiversity. Firm, proportionate, and integrated law enforcement, combined with preventive approaches, is essential to achieving effective wildlife protection.